DESA BLIMBINGSARI SEBAGAI POTENSI UNGGULAN WISATA RELIGI DI KABUPATEN JEMBRANA - I Putu Sagita Jaya Utama (UHN IGB Sugriwa Denpasar, 2021)
The potential for tourism activities in Jembrana Regency deserves attention to be a choice of attractions for tourists who will travel with various motivations. The purpose of writing this article is to discuss and provide a systematic view in a scientific framework to describe Blimbingsari Village as a leading potential in the development of religious tourism in Bali, especially in Jembrana Regency. However, the scarcity of literature that discusses the topic of tourism potential, especially in Jembrana, is a problem that needs to be solved, especially for academics. Supported by several literatures that closely related to the research topic, this paper provides a descriptive analysis of the available and relevant articles in the field of tourism with a special emphasis on religious tourism. So that there is a need for high synergy between Jembrana tourism stakeholders, among the Regional Government, local community, and tourists in utilizing the potential that exists in Blimbingsari Village as a leading tourist attraction.